A glimpse of academic staff health behavior on diet type and physical activity at Austrian universities: first findings from the "Sustainably Healthy - From Science 2 Highschool & University" study - Katharina C. Wirnitzer; Katharina C. Wirnitzer; Katharina C. Wirnitzer; Mohamad Motevalli; Mohamad Motevalli; Derrick R. Tanous; Derrick R. Tanous; Gerold Wirnitzer; Karl-Heinz Wagner; Manuel Schätzer; Clemens Drenowatz; Armando Cocca; et al. (Frontiers Media S.A., 2023)
BackgroundThe association between lifestyle and health status highlights the importance of assessing health-related behavior in different populations. This multidisciplinary study aimed to examine the health behavior of academic staff of Austrian colleges and universities, with a specific focus on diet types (vegan, vegetarian, omnivorous) and physical activity (PA) reports.MethodsFollowing a cross-sectional study design incorporating an online survey, a sample of 1,041 academics from 52 institutes (mean age: 46.4 years) provided data on sociodemographic characteristics, dietary patterns, PA behavior, and other lifestyle behaviors (smoking, alcohol intake, etc.).ResultsThe prevalence of vegetarian and vegan diets was 13.2 and 2.0%, respectively, and 33.2% of participants had excess body weight (BMI ≥ 25). The majority of participants (88.5%) reported regularly engaging in leisure-time PA, but 18.6% were active members of sports clubs. No difference between females and males was observed in diet type and the type of sport participation (p > 0.05). Participants with a mixed diet had a higher BMI than vegetarians and vegans (p < 0.05). Leisure-time PA participation was associated with more frequent fruit and vegetable intake (p < 0.05). The prevalence of smoking and alcohol intake was 13.1 and 73.5%, respectively, without any difference between dietary or sports participation subgroups (p > 0.05).ConclusionThe present study provides an overview of the social trends in vegan and vegetarian diets linked to health behaviors in tertiary educational settings. Findings can be used by health scientists, decision-makers, and multipliers in health and education to improve public health.